RESOURCE EFFICIENCY WITHIN SEMI-CONTINUOUS PRODUCTION: AN APPROACH TO ASSESS PROCESS-INHERENT RESOURCE DISSIPATION - Meier, Horst; Bakir, Dennis; Krückhans, Björn (Management and Production Engineering Review, 2013)
Within classic German manufacturing structures, costs of resources exceed all other cost factors by 46% [1]. Solitary focus on energy or labor costs as sources to raise companies profit no longer seems adequate. Nowadays material costs of the manufacturing industry are about 500 billion euro per year, connected with a saving potential of 100 billion euro per year. Also the belonging for sustainably produced products is raising and becoming a factor for guaranteed purchases [2]. A small and medium-sized enterprise fitted approach, which ensures to increase the transparency of internal process structures and allows a resource driven, ecological and economical assessment, is the main subject of this article.